A PRELIMINARY STUDY OF MEDICATED SURMEH (A NATIVE MASCARA POWDER) BY BIOLOGICAL METHOD - H. Mohsenin; Kh. Moradpour (Tehran University of Medical Sciences, 1974)
Trachoma, especially its complications, is more prevalent in females than in males. In some of the rural areas of Iran, the use of "Surmeh" is a prevalent practice. A biological test was carried out to determine the benefit of using this social custom by means of medicated surmeh for the control of trachoma and other infectious eye disease. Surmeh is smoked carbon powder, with a little oil added, which is used for beautifying the eye-lashes and eye-lids of women. Surmeh could transmit bacterial eye diseases, but its effect on the transmission of trachoma is not yet proven. In preparing medicated Surmeh almond oil is used, but other cheap, non-allergiant oils may be substituted. Seventy tests for three kinds of medicated surmeh were performed, i.e., 1. surmeh plus 1% aureomycin; 2. surmeh plus 3% aureomycin; 3. surmeh plus about one-thousandth methylene blue. The biological test is the same as the usual bacterial sensitivity test, i.e., a stock isolated sensitive staphylococcus is cultured on blood agar plate and round disc papers ,with eye secretion are put on the plate. The tests showed that all three medicated surmeh were effective and have considerable residual effects up to 8 hours. In few occasions the residual effect was lasting even up to 16-23 hours. The residual effects of medicated surmeh are nearly the same as those of antibiotic eye ointments. Medicated surmeh may be used for the treatment of blepharitis. It seems that medicated surmeh is also effective in trachoma control, especially for the prevention of trichiasis. Medicated surmeh can be prepared in the field by making a condensed oil suspension of the effective drug and mixing 2-3 drops in each of the women's surmeh pots. Health education is needed for the proper use of surmeh in areas where its use is common, and precautions must be taken to prevent the spreading of this social custom.